Light permanence wrap prints produced with CMYK UV inkjet inks - Damir Modrić; Marko Morić; Ivana Bolanča Mirković; Ana Lešić; Igor Majnarić (Tehnički Glasnik, 2017)
Nowadays, Inkjet technology has become one of the most widespread printing technologies in car industry (car wrapping = printing and wrapping the whole vehicle or a part of a vehicle in printed foil). Printed wrap foils are, after the wrapping process, exposed to the same conditions as a lacquered vehicle: intensive sunlight, high and low temperatures, rainfall, snow, ice, particles or bugs that the vehicle encounters while driving, etc. In this paper we tested different types of wrapping foils (Orajet, 3M Scotchcal and 3M Controltac) and solvent inkjet inks to investigate the influence of different types of wrap foils on the real reproduction of UV ink jet coloured imprints, as well as their stability fluctuations during ageing. The inkjet prints age faster under the influence of UV light (Xenon lamp in SolarBox) in a period of 240 hours. The results show that the 3M Scotchcal foil has the best CMYK stability.